La Nueva gramática de la lengua española (2009) entre la tradición y la modernidad - Pawlik, Janusz (Neophilologica, 2012)
This paper is intended to present the newest edition of Spanish grammar elaborated by the Association of the Spanish Language Academies from the Spanish speaking countries. This latest edition is partly a continuation of the old Spanish grammatical tradition and partly a completely new approach to grammatical problems.